APLIKASI PERSAMAAN LINIER METODE SIMPLEKS PADA PEMBANGUNAN PERUMAHAN - -, Burhanuddin (Fakultas Sains dan Teknologi UIN ALauddin, 2011)
This research is about (1) the application of the linier program of the simplex method on housing development type: 36, 45 and 54 ; and (2) the way to minimize resources and maximize profit on the certain type of housing using mathematics program and analysis.The method used was simple linier program, in order to mathematically the development program wich can assist the decision maker of the developer companies in maximizing profit even though with limited resources. The analysis of the program can be complete manually or using computer program.Â Keywords : program, linier, simpleks, housing, resource